2007
DOI: 10.1088/0031-9155/52/16/015
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic analysis of the slotted-tube resonator with a circular cross section for MRI applications

Abstract: In this paper we present electromagnetic (EM) analysis of the unloaded slotted-tube resonator (STR) with a circular cross section, using the finite element method (FEM) and method of moments (MoM) in two dimensions. This analysis allows the determination of the primary parameters: [L] and [C] matrices, optimization of the field homogeneity, and simulates the frequency response of S(11) at the RF port of the designed STR. The optimum configuration is presented, taking into account the effect of the thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…This coil is oriented perpendicular to B 0 . The body of the mouse was aligned along B 0 and the leg was positioned within the solenoid coils .…”
Section: Methodsmentioning
confidence: 99%
“…This coil is oriented perpendicular to B 0 . The body of the mouse was aligned along B 0 and the leg was positioned within the solenoid coils .…”
Section: Methodsmentioning
confidence: 99%
“…A series of previously published planar micro-sensor designs 20,34 along with some novel designs were manufactured to demonstrate the capability of using CNC micro-milling for NMR micro-coil development. In addition, a series of microstrip designs 34 were optimized for analysing 13 C-labelled D. magna adults as well as a slotted-tube resonator (STR) 35 for the study of neonates. It was found that cavities and sample holders could be made from copper/Teflon sheet at the same time as the coils were made.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hybridising MoM and FEM produces an exceptionally capable full-wave numerical technique that is particularly suited for modelling MRI RF coils and analysing RF field behaviour. The hybrid MoM/FEM used by our group is commercially available from FEKO, and its mathematical formulation has been discussed extensively (84,(97)(98)(99)(100)(101)(102)(103). For the purposes of illustration, we will give two examples to demonstrate the effectiveness and accuracy of the hybrid MoM/FEM method for MRI RF coil modelling.…”
Section: Hybrid Mom/femmentioning
confidence: 99%